Ten books that shaped the British empire : creating an imperial commons - Burton, Antoinette M., 1961-; Hofmeyr, Isabel (Duke University Press, 2014)
Looking at ten books that shaped the modern British Empire, the contributors examine imperial classics, anticolonial blockbusters, and a range of pamphlets, assessing the effects of each one on key aspects of imperial history.